2019
DOI: 10.1177/0961203319864168
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of systemic lupus erythematosus in Colombia: data from the national health registry 2012–2016

Abstract: Introduction Registries are essential to keep track of systemic lupus erythematosus (SLE) epidemiology and to provide better care to patients. The Colombian Ministry of Health has adopted a registry (SISPRO) to gather comprehensive information coming from the Colombian health system, which provides close to universal coverage (around 95%). The information collected from SISPRO is available for scientific analysis. Objectives We used data collected by SISPRO to estimate prevalence and specific characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 24 publications
2
18
0
3
Order By: Relevance
“…[ 1 ] Systemic lupus erythematosus (SLE) is one among the most common autoimmune disorders affecting females of child-bearing age. [ 2 ] As stated in other studies, research concerning SLE in pregnant women have often been limited to a particular ethnic group, or most of the time to a specific region. [ 3 , 4 ] Therefore, to generalize this issue, Bundhun et al clearly demonstrated the impact of SLE on maternal and fetal outcomes through a meta-analysis including various studies from different parts of the globe and included studies which were published between the years 2001 and 2016.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Systemic lupus erythematosus (SLE) is one among the most common autoimmune disorders affecting females of child-bearing age. [ 2 ] As stated in other studies, research concerning SLE in pregnant women have often been limited to a particular ethnic group, or most of the time to a specific region. [ 3 , 4 ] Therefore, to generalize this issue, Bundhun et al clearly demonstrated the impact of SLE on maternal and fetal outcomes through a meta-analysis including various studies from different parts of the globe and included studies which were published between the years 2001 and 2016.…”
Section: Introductionmentioning
confidence: 99%
“…National data from Colombia national health care register estimated a prevalence of 91.9/100,000 subjects, being more frequent in women (89% cases). When adjusted, female and male prevalence has a 7.9:1 female:male ratio [5]. The prognosis of SLE has vastly improved in recent years, and this is thanks to improved diagnostic and therapeutic methods.…”
Section: Introductionmentioning
confidence: 99%
“…We have described searching methods previously. [8][9][10][11] Due to recent updates on the database, the currently available information comprises only the period between 2015 and 2019. Briefly, we obtained the information for the whole country, for the period between January 1 st 2015 and December 31 th 2019.…”
Section: Palabras Clavementioning
confidence: 99%